A model for the study of the growth of body area in beef cattle - Parés-Casanova, Pere M. (2018)
Estimation formulas have been established for the establishment of body surface area (BSA), using live weight (LW) and body length for calculation. The objective of this work was to compare four estimation formulas of the BSA – Mitchell [0.09 × LW0.69], Brody [0.14 × LW0.57], Johnson et al. [0.235 × LW0.49], Moulton [0.158 × LW5/8] and Hogan and Skouby [LW0.4 × (body length)0.6 × 217] – and three non-linear models – logistic [–y=a/(1 + be-cx)], Gompertz [y=a*exp(b*exp(cx))] and von Bertalanffy [y=a(1-be-cx)] – in terms of their ability to describe the growth of BSA in beef cattle and to detect the best estimator. Fifty-three meat cattle (20 males and 33 females) were used, mostly “Bruna dels Pirineus” and their crosses, with ages between 205 and 407 days, estimated live weight of 543±74 kg, which were slaughtered in a commercial abattoir. After the skinning, a photograph of the extended leather was obtained and using digital methods the BSA was calculated. The BSA was 3.79±1.37 m2 (range 2.55-8.12 m2). Hogan and Skouby formula appeared as the most accurate estimating formula with a determination level of over 58%, the difference in the values being due probably to the surface of the head and the distal parts of the limbs which were not considered in the study, as they were separated in the process of skinning. Among the non-linear models, the best fit was the logistic one, but with a much lower determination level of around 2%. Data shows, moreover, that, in beef cattle, body area has not reached yet its definitive development at 400 days of age. This fact should be considered when setting surface body development and new estimating formulas.